Kadar Laktosa, Gula Reduksi, dan Nilai pH Yoghurt dengan Penambahan Bekatul Selama 15 Hari Penyimpanan Refrigerasi - Dyah Laksito; Rizza Wijaya; Rizki Amalia Nurfitriani (Jurnal Ilmu Peternakan Terapan, 2020)
This study aimed to determine the effect of 15 days refrigeration storage on lactose content, reducing sugars, and the pH value of yoghurt by addition of rice bran. The experimental design used a completely randomized design (CRD) for 4 treatments and 5 replications. The treatments consisted of T0 (without storage), T1 (5 storage days), T2 (10 storage days), and T3 (15 storage days). The results showed that lactose content, reducing sugar, and pH value of yoghurt were analyzed by analysis of variance (ANOVA). If there were significant differences, then further tested by Duncan's Multiple Range Test. Yoghurt by addition of rice bran stored for 15 days in the refrigerator could reduce lactose content and pH values and increased the level of reducing sugar, so that be able to maintain the quality and freshness of yoghurt.